Understanding Common Learner Errors: A Contrastive Analysis Approach Through Pre-Service Teachers Interview - Pratama, Ahmad Rizky Ardi; Azzahra, Fatimah; Khoiriah; Wahyuni, Larasati Dwi; Hafizhah, Maulia; Harahap, Nurhapsi; Pratiwi, Putri Adinda; Nasution, Raisa Rahmi; Tobing, Sarah Davina L.; Bahar, Tanzila; Azra, Tsabitha (PT. Kreasi Karya Majakata, 2025)
This study examines prevalent linguistic inaccuracies encountered by individuals learning the English language, as well as the perceptions and methodologies employed by pre-service educators in addressing these inaccuracies through contrastive analysis. The adopted methodology is qualitative, utilizing contrastive analysis to facilitate a comprehensive understanding of the frequent errors and the approaches that pre-service teachers can utilize to correct them. The results indicate that learners commonly struggle with various elements, including grammatical issues, pronunciation errors, interference from their native language, limited vocabulary, and psychological challenges such as anxiety and diminished self-confidence. Through semi-structured interviews conducted with 20 pre-service teachers, the research pinpointed effective strategies employed, which comprise explicit correction techniques, phonetic drills, thematic vocabulary instruction, and the establishment of a nurturing classroom atmosphere. The findings underscored the necessity for enhanced teacher training, the incorporation of technology, student-centric methodologies, cultural awareness, and ongoing professional development for educators to elevate the effectiveness of language instruction.